Study on flow structure of tandem multiple jets under the effect of regular waves. (1st December 2020) - Xu, Zhenshan; Zhang, Yuling; Chen, Yongping
Abstract: The effect of regular waves on the flow structure of tandem multiple jets is investigated experimentally in this study. The tandem multiple jets are discharged vertically into the wave flow. The particle image velocimetry (PIV) technique is employed to measure the flow field of tandem multiple jets. The movement of tandem multiple jets in regular waves is defined starting from the orifices as the separated region, the mixing region and the mixed region. These three regions are distinguished by the mixing point and the mixed point, respectively. The results show that the wave-to-jet velocity ratio R wj is the most important parameter to characterize the effect of regular waves on multiple jets, affecting the mixing point location, the vertical velocity decay and the cross-sectional distribution of vertical velocity. Using curve-fitting, the formulas estimating the effects of wave-to-jet velocity ratio ( R wj ) on the mixing point location and the vertical velocity decay are derived. This study reveals that the regular wave has a positive effect on the mixing and dilution of tandem multiple jets. Highlights: Flow field of multiple jets in regular waves are measured using PIV technology. The wave-to-jet velocity ratio R wj is a key parameter affecting multiple jets. The multiple jets movement is divided as separated region, mixing region and mixed region. The formulas for mixing point location and vertical velocity decay are established.